Efficacy of melatonin and letrozole combination therapy compared to letrozole alone in the treatment of symptomatic endometrioma in infertile women - Khatun, M. Sumyara; Islam, Aminul; Islam, Tahmida; Islam, M. Ariful; Ishrat, Shakeela; Deeba, Farzana; Jahan, Nishat; Banu, Jesmine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Endometriosis is an estrogen-driven inflammatory condition involving endometrial tissue growth outside the uterus. Letrozole, an aromatase inhibitor, lowers estrogen levels to reduce pain and lesion size. Melatonin offers additional benefits through its antioxidant, anti-inflammatory, and anti-proliferative effects on endometrial tissue. The present study was conducted to compare the effects of a combination of melatonin and letrozole with letrozole alone in infertile women with symptomatic endometrioma. Methods: This randomized controlled trial was conducted in the Department of Reproductive Endocrinology and Infertility of Bangabandhu Sheikh Mujib Medical University from July, 2023 to June, 2024. Total 40 infertile women with symptomatic endometrioma were included in this study. They were randomly allocated to receive either tab. letrozole 2.5 mg, twice daily plus tab. melatonin 3mg, 3 tablets at night daily or only tab. letrozole 2.5 mg, twice daily for 3 months. Results: Mean VAS score (6.88±2.39 vs 2.64±1.96) and mean size of endometrioma (3.77±1.22 vs 3.05±1.17 cm) were significantly decreased after 3 months of treatment with melatonin and letrozole combination therapy and mean VAS score (7.11±1.81 vs 3.22±1.89) and mean size of endometrioma (3.81±1.00 cm vs 3.27±0.85) were also significantly decreased after 3 months of treatment with letrozole alone group .But there were no statistically significant difference in terms of reducing pain score and size of endometrioma when compared between two groups. Conclusions: Melatonin and letrozole combination therapy compared to letrozole alone provide similar efficacy on symptomatic endometrioma in terms of reduction of pain score and size of endometrioma.